Un printemps arabe ? L’émulation protestataire et ses limites - Michel Camau (L’Année du Maghreb)
The term “Arab Spring” has become patently obvious to describe a process of protest emulation unprecedented in the region. Such metaphor owes much to media fluency. However, issues raised by the “Arab Spring” cannot be limited to this type of acceptations. They refer to both the limits of protest emulation and those of our own knowledge. No one had foreseen the “Tunisian Revolution”, no more than its spinoffs in Egypt and other Arab countries. The protest momentum spread but it did not occur in the same form or with the same intensity elsewhere, and above all, it did not produce the same effects. There is an overall margin of uncertainty, which may be elucidated through consideration of three types of problems, closely related but analytically distinct: the ambiguity of the “revolution” label, the surprise generated by events regarded afterwards as inevitable, and the effects of demonstration and context in the protest cycle. We attempted to address those issues based on the idea of crisis of legitimacy as a criterion of differentiation between the “Arab revolutions”, and of pluralistic ignorance with regard to the unclear preferences of those in authority positions and finally of the rulers’ learning in relation to their methods of prevention and management of crises of legitimacy.